Publishing as an Agricultural Economist: Thoughts on Why, Where and How - Thomas Heckelei (German Journal of Agricultural Economics (GJAE), 2010)
Publishing provides the basis for scientific communication and thereby supports further scientific advances. Successfully publishing articles in peer-reviewed journals has become increasingly important for building an academic career, also for agricultural economists. The aim of this article is to motivate and encourage young agricultural economists with limited or no publishing experience to write research articles and submit them to peer-reviewed journals. In order to achieve this, some arguments are given 'why' peer-reviewed publishing is a worthwhile exercise. Then a look at journal quality and choice in our discipline addresses the 'where'. Finally a significant part is devoted to 'how' to write a paper suggesting a potentially useful sequence of steps and discussing elements and style of a typical empirical research article.
Keywords: 330; Wissenschaftliches Arbeiten; Agrarökonomik